John Adams : a Life. - Ferling, John (Oxford University Press, USA, 2010)
John Ferling has nearly forty years of experience as a historian of early America. The author of acclaimed histories such as A Leap into the Dark and Almost a Miracle, he has appeared on many TV and film documentaries on this pivotal period of our history. In John Adams: A Life, Ferling offers a compelling portrait of one of the giants of the Revolutionary era. Drawing on extensive research, Ferling depicts a reluctant revolutionary, a leader who was deeply troubled by the warfare that he helped to make, and a fiercely independent statesman. The book brings to life an exciting time, an age in.